2015
DOI: 10.1016/j.neuron.2015.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Subnetwork-Specific Homeostatic Plasticity in Mouse Visual Cortex In Vivo

Abstract: SummaryHomeostatic regulation has been shown to restore cortical activity in vivo following sensory deprivation, but it is unclear whether this recovery is uniform across all cells or specific to a subset of the network. To address this issue, we used chronic calcium imaging in behaving adult mice to examine the activity of individual excitatory and inhibitory neurons in the same region of the layer 2/3 monocular visual cortex following enucleation. We found that only a fraction of excitatory neurons homeostat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

23
146
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 113 publications
(169 citation statements)
references
References 57 publications
23
146
0
Order By: Relevance
“…Reducing the levels of inhibition onto excitatory neurons is consistently observed following loss of input in cortex [10,[22][23][24][25][26][27] and has been hypothesized to be a first step in circuit reorganization following input loss [28]. Changes in inhibition can occur via a reduction in the number [12,22,24,26,27,[29][30][31][32][33] or strength of inhibitory synapses onto excitatory cells [33], as well as a reduction in the firing rate of the inhibitory neurons following deprivation either temporarily during development [11,34] or for longer time courses in adulthood [29]. Changes in inhibitory tone may be modulated via astrocytes [35] or NMDA receptor input [36].…”
Section: Mechanisms Of Homeostatic Stabilizationmentioning
confidence: 99%
See 2 more Smart Citations
“…Reducing the levels of inhibition onto excitatory neurons is consistently observed following loss of input in cortex [10,[22][23][24][25][26][27] and has been hypothesized to be a first step in circuit reorganization following input loss [28]. Changes in inhibition can occur via a reduction in the number [12,22,24,26,27,[29][30][31][32][33] or strength of inhibitory synapses onto excitatory cells [33], as well as a reduction in the firing rate of the inhibitory neurons following deprivation either temporarily during development [11,34] or for longer time courses in adulthood [29]. Changes in inhibitory tone may be modulated via astrocytes [35] or NMDA receptor input [36].…”
Section: Mechanisms Of Homeostatic Stabilizationmentioning
confidence: 99%
“…There is experimental evidence for three balance parameters: firing rate homeostasis, subthreshold activity homeostasis, and synaptic weight homeostasis, and any of these three parameters, when incorporated into the appropriate theoretical model, may stabilize the network to prevent pathological neuronal dynamics or learning [1,3,4,[47][48][49][50][51][52][53][54][55][56][57][58]. First, firing rate homeostasis was initially described with the first experimental evidence of synaptic scaling [5], and altering cellular [59] and network firing rate has consistently evoked a response of the induction of homeostatic mechanisms [5,7,11,12,29,60]. Several studies have now demonstrated that neurons will recover their firing rates in vitro [5,59] and in vivo [11,12,29,60], in parallel with the induction of homeostatic mechanisms, and that neurons in the developing visual cortex have a firing rate set point to which they return after deprivation [60].…”
Section: Parameters Of Homeostatic Balancementioning
confidence: 99%
See 1 more Smart Citation
“…In this issue of Neuron, Barnes et al (2015) show that visual deprivation-induced homeostatic plasticity invokes specific changes among select categories of V1 neurons. The brain has evolved extensive mechanisms to maintain stable activity levels in the face of fluctuating synaptic drive.…”
mentioning
confidence: 93%
“…One way is through homeostatic plasticity or the ability to fine tune the excitability of specific neuronal networks (Turrigiano, 2012). In this issue of Neuron, Barnes et al (2015) addressed whether homeostatic recovery of cortical activity in response to visual deprivation reflects the involvement of specific subsets of neurons and how those cells contribute to the plasticity of the larger circuits in which they are embedded.…”
mentioning
confidence: 99%